Prawne uwarunkowania uzyskania wsparcia na prowadzenie agroturystyki z Programu Rozwoju Obszarów Wiejskich 2014-2020 - Kapała, Anna (Wydawnictwo Naukowe UAM, 2015)
The deliberations presented in the paper aim to establish whether and to what extent support can be offered under the Rural Development Programme 2014-2020 to farmers planning or already engaged in agritourism. The categorisation of different types of agritourist activity provided in the Programme has been analysed. Regulation (EU)1305/2013 does not provide for any special support for agritourism, but only a business start-up aid (Article 19.1.a) or for investments and creation of non-agricultural activi-ties (Article 19.1.b). It leaves the decision of detailed criteria qualifying for the support to Member States, but makes no mention of the role of agritourism in the development of rural areas, as business conducted alongside ordinary agricultural activity, excluded from the scope of the Act on Freedom of Business Activity.

L’obiettivo della discussione è di determinare se e in quale misura il Programma di Sviluppo rurale 2014-2020 preveda il sostegno agli agricoltori che stanno per avviare oppure stanno già esercitando l’attività agroturistica. Ad analisi sono state sottoposte le misure definite nel Programma nell’ambito della diversificazione dell’attività. Il Regolamento 1305/2013 non prevede sostegno separato all’agriturismo, ma aiuti all’avviamento di imprese (art. 19 paragrafo 1 lettera a) oppure aiuti agli investimenti nella creazione e nello sviluppo di attività extra-agricole (art. 19 paragrafo 1 lettera b). Spetta agli Stati membri definire i criteri specifici per concedere l’aiuto. Tuttavia, il ruolo dell’agriturismo per lo sviluppo rurale, inteso come attività che affianca l’attività agricola, esente dall’essere soggetta alle disposizioni di legge sulla libertà di iniziativa economica, non è stato preso in considerazione.
Legal determinants of receiving support for an agritourism business from the Rural Development Programme 2014-2020
La possibilità di ottenere dei finanziamenti per l’apertura di un agriturismo con il Programma di Sviluppo rurale 2014-2020